Analiza form zatrudnienia w Polsce - Januszewska, Małgorzata J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Of course, there is no universal answer when it comes to deciding which form of agreement is the best, as it depends on the type of work. If it bears the hallmarks of an employment relation, even though costs for both an employer and an employee are significant, it is worth concluding an employment contract because the privileges it confers are not comparable with other agreements. In such a situation service contract as the sole source of income does not cause any savings for an employer but only increases the cost for an employee. It can be stated with absolute certainty that what makes an employment contract more attractive are more likely vacations than the costs associated with the contributions which are unlikely to bring real benefits in the form of a decent pension. When it comes to an agency contract, it is beneficial for both sides only for the first two years of existing of the enterprise and only if the salary contains more than just a provision. After two years, the only side saving money is an employer. So if it is possible, it pays off to include other types of civil contracts as they leave more net resources to use if somebody has another source of income or is a student.
Keywords: koszty zatrudnienia; umowa agencyjna; umowa o dzieło; umowa o pracę; umowa zlecenia; zatrudnienie